Efficiency frontier and matching process on the labour market: Evidence from Tunisia - Anis Bou Abid; Imed Drine (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper studies the determinants of the inefficient functioning of the Tunisian labour market. The study takes advantage of recent developments in the stochastic frontier techniques and estimates the matching function for Tunisia using disaggregated data. We include control variables as determinants of matching efficiency and regional disparities. We confirm that the persistently high rate of unemployment is the result of not only excess labour supply but is also related to a shortfall between supply and demand, i.e. sector, location, qualification.
Keywords: J64; 330; labour market; structural unemployment; technical efficiency; matching across regions; developing country; Arbeitsmarkt; Strukturelle Arbeitslosigkeit; Technische Effizienz; Matching; Tunesien